Legal Position and Health Rights of Adopted Children with Different Parents of Citizenship in the Legal System in Indonesia - Agatha Chriestie Tarigan (LEGAL BRIEF, 2022)
The importance of the registration of adoption is that the adopted child protection. The importance of the protection of children raised, namely, as an adopted child or a child is the subject of law and therefore may impose any parent well is, couples foreigners (foreign citizens) with foreigners or citizen (Citizen Indonesia) with citizen and foreign citizen (Citizen foreign) and citizen (Citizen Indonesia) are required to register the children raised , in order to provide protection for the child in terms of rights in inheritance and obtain legal standing.